Strengthening Early Nursing Practice: Psychometric Validation of the Turkish Version of the Professional Interpersonal Competence Scale - Ozalp, Cemal (Wiley, 2026)
Objective: To culturally adapt the Professional Interpersonal Competence Evaluation Scale for novice nurses in Turkiye. Background: This methodological study aimed to translate, culturally adapt, and evaluate the psychometric properties of the Professional Interpersonal Competence Evaluation Scale for novice nurses. Study Design and Methods: This methodological study was conducted with 450 nurses working in two public hospitals between October and December 2024. The construct validity of the scale was evaluated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Reliability was assessed using Cronbach's alpha, McDonald's omega, and split-half reliability coefficients. Results: The Kaiser-Meyer-Olkin value was 0.929, and Bartlett's test of sphericity was significant (chi(2) = 6852.706, p < 0.001), indicating sampling adequacy for factor analysis. EFA revealed a two-factor structure consisting of 26 items, explaining 44.485% of the total variance, with factor loadings ranging from 0.403 to 0.789. CFA results supported the two-factor model with acceptable fit indices (chi(2)/df = 4.62, RMSEA = 0.078, CFI = 0.94, TLI = 0.92). Item-total correlations ranged from 0.353 to 0.753 (p < 0.001). The internal consistency of the scale was high (Cronbach's alpha = 0.945; McDonald's omega = 0.948). Conclusion: The results indicate that the Professional Interpersonal Competence Evaluation Scale for novice nurses is a reliable and valid evaluation tool for Turkiye.
Keywords: Beginning Nurse; Cultural Adaptation; Interpersonal Competence; Nurses; Scale